Cardiac Involvement in a Fetus With Vein of Galen Aneurysmal Malformation, Diagnosis, and Treatment: A Case Report - Mohammad Taghi Majnoon; Behdad Gharib; Sara Memarian; Azade Rastgar; Mahsa Naemi; Alireza Golbabaei (Mazandaran University of Medical Sciences, 2021)
Vein of Galen Aneurysmal Malformations (VGAMs) are severe and rare congenital brain vasculature anomalies, which causes high mortality and morbidity in fetuses, neonates, and infants. It can be identified in the pregnancy period with fetal echocardiography. We report a case of VGAMs with severe cardiac manifestations in the fetus of a pregnant woman at the 28th week of gestational age.